WAKAF TUNAI DALAM PERSPEKTIF MAJELIS ULAMA INDONESIA (Analisis Terhadap Fatwa MUI No.2. Tahun 2002 Tentang Wakaf Uang) - Dr. Armiadi Musa (Universitas Islam Negeri Ar-Raniry, 2017)
MUI fatwa against legal permissibility (jawaz) wakaf cash has the basis of consideration nash argument (hadith Ibn Umar) which reads ihbas ashlaha wa sabbil tsamarataha. The basic considerations of MUI also exist in the aspect of its mashlahah, that the money waqf has flexibility (flexibility) and the great benefit that is not owned by other objects, in addition to its easiness in capturing waqif. The MUI sees it necessary to the development of meaning because of the substance of that understanding is the necessity of ta'bid on the substance of mawquf substance (baqa 'ainih). So the element of his devotion is to emphasize only aspects of matter not including the nature of things as well as the eternal intrinsic value of money (baqa 'ashlih). So with the development of understanding of this wakaf, is expected to open opportunities for reinterpretation of the meaning of waqf more relevant in the economic development of society. MUI also sees the need for the addition of